2011
DOI: 10.1016/j.jcv.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Primary HIV-1 drug resistance in the C-terminal domains of viral reverse transcriptase among drug-naïve patients from Southern Brazil

Abstract: Major resistance-conferring mutations to NNRTI were detected in 10% of RT connection domain viral sequences from treatment-naïve subjects. We showed for the first time that the presence of specific polymorphisms can constrain the acquisition of definite resistance mutations in the connection and RNase H subdomains of HIV-1 RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Several studies have reported an increase in HIV-1C prevalence in that region. [8][9][10][11][12][13][14][15][16] In the city of Rio Grande, one of the foci of this study, such an increase is clearly evident: from 22% in 2002 to 56% in 2010. 16,17 The introduction of highly active antiretroviral therapy (HAART) in HIV-infected patients is associated with a marked reduction in morbidity and mortality.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Several studies have reported an increase in HIV-1C prevalence in that region. [8][9][10][11][12][13][14][15][16] In the city of Rio Grande, one of the foci of this study, such an increase is clearly evident: from 22% in 2002 to 56% in 2010. 16,17 The introduction of highly active antiretroviral therapy (HAART) in HIV-infected patients is associated with a marked reduction in morbidity and mortality.…”
Section: Introductionmentioning
confidence: 78%
“…The CN N348I and the RNH Q509L mutations, not seen in untreated subjects, 14 were found in patients under virological failure, sustaining the importance of these mutations in drug resistance. 40,41,[45][46][47] Interestingly, both viruses carrying Q509L were HIV-1C.…”
Section: Novel Hiv-1 Rt C-terminal Mutationsmentioning
confidence: 86%
See 3 more Smart Citations